METAPHORS ANALYSIS IN BRING ME THE HORIZONâ€™S â€œAMOâ€ ALBUM SELECTED SONG LYRICS - Nurman, Moh.; Dindiana, Lidia (Universitas Islam Lamongan, 2021)
The aims of this research is to know the types of metaphors found in Bring Me The Horizonâ€™s â€œAmoâ€ album selected songâ€™s lyrics and what is the intended meaning of the songâ€™s lyrics. There are two research questions. They are: 1) what types of metaphors are found in Bring Me the Horizonâ€™s selected song lyrics? 2) What is the intended meaning of the songâ€™s lyrics? The reason behind this research was conduct is to get more knowledge about figurative language especially metaphor and how it works in the literary world. This research uses descriptive qualitative method in analyzing the lyrics. The result of this research shows six types of metaphors by Newmark. Those are dead, clichÃ©, stock, recent, original metaphor and simile. Two out of their three songs of Bring Me the Horizon, that is Medicine and In the Dark use dead metaphor and simile the most. It is then concluded that the intended meanings of their three songs is to tell other people who ever felt belittled, have social issues or being looked down to keep going and not affected by those hurtful words. In other words, Bring Me the Horizon uses the function of figurative language especially metaphor to express their message and applied them into their works. Â Keywords: Metaphor, meaning